EFFECT OF AMBIENT TEMPERATURE ON FOOD, NITROGEN AND ENERGY INTAKE OF THE FIELD-VOLE, MICROTUS ARVALIS, UNDER DIFFERENT CONDITIONS OF DAYLIGHT RATIO AND FEEDING - Caillol, Monique; Martinet, Lise; Monnerie, Régine (HAL CCSD, 1976)
International audience